Comparison of two methods of using normal saline and lidocaine gel during laryngeal mask airway insertion on hemodynamic symptoms and emergence reactions in patients undergoing cataract surgery: A double-blind randomized controlled trial - Jahromi, Masoud Ghanei; Reza Sahraei; Keshavarz, Sahar; Kalani, Navid; Taban, Samira (International Journal of Psychosocial Rehabilitation, 2020)
Background and aim: Due to high sensitivity, eye surgery should be accompanied by the least reaction and strain of the patient. On the other hand, sore throat, cough and nausea can reduce patient satisfaction and limit postoperative activities. Therefore, the present study aimed to compare the two methods of using normal saline and lidocaine gel during laryngeal mask airway (LMA) insertion on the hemodynamic symptoms and emergence reactions in patients undergoing cataract surgery. Methods: This double-blind randomized controlled trial was conducted on 120 patients undergoing cataract surgery. The patients were randomly divided into two groups of lidocaine gel (n=60) and normal saline (n=60). Systolic and diastolic blood pressure, heart rate and arterial oxygen saturation (SaO2) were measured before and immediately after induction, and 5, 15 and 30 minutes after surgery, as well as in recovery. In addition, episodes of cough, sore throat, nausea, and vomiting at recovery, 1, 6, 12, and 24 hours after surgery were recorded in the ophthalmology department. Results: The results of the current study showed that the groups did not differ significantly in terms of demographic characteristics. There was no significant difference between cough, nausea and heart rate and SaO2 levels in 5 minutes after surgery and recovery on LMA after withdrawal, but there was a significant difference in SaO2 level. The SaO2 level was increased 15 to 30 minutes after surgery in the normal saline group. Conclusion: The results of this study showed that the use of lidocaine gel to facilitate airway insertion has no effect on postoperative cough and sore throat. Future studies are recommended to examine this finding in surgical procedures with further LMA facilitators.